POLA PENYELESAIAN PERSELISIHAN MENURUT RASUL PAULUS DALAM 1 KORINTUS 3:1-9 - Daniel Sarwono (Sekolah Tinggi Teologi Arastamar Bengkulu, 2016)
1 Corinthians This letter is a letter written by the Apostle Paul addressed to the church in Corinth in 55 CE during his second missionary journey. The writing of this letter is motivated by several things, one of which is disputes. The city of Corinth was a metropolitan city with a strategic location so that many people came to Corinth to trade. In addition, the city of Corinth was also known for its extraordinary level of crime. All crimes are committed openly there. For Paul, the disputing church is a church that is not yet mature in the faith, so that they are still dominated by the spirit of division, unable to focus on the source of growth. In this case Paul provided a solution to overcome the problem of disputes that occurred among the Corinthians, namely applying the pattern of dispute resolution according to the Apostle Paul. It is hoped that through this article can help the lives of believers in overcoming disputes in the Church.